Effect of duty cycle on ozone production using DBDP cylindrical reactor. (May 2019) - Yulianto, E; Aryadi, R; Zahar, I; Sasmita, E; Restiwijaya, M; Kinandana, AW; Arianto, F; Nur, M
Abstract: Ozone production using DBDP technology used pulse high voltage to generate ozone. The duty cycle has been used the variations of 10%, 30%, 50%, 60% of the 350 Hz as installed frequency. The DBDP reactor constructed by using cylinder-cylindrical electrode configuration. The inner electrode was made by stainless steel mesh with a length of 19 cm, and the outer electrode was aluminum foil with a length of 19 cm. The barrier was made of tube pyrex glass. Ozone is generated utilizing air as an oxygen-containing gas source with atmospheric pressure and a flow rate of 10 L/minute. The results show that using 10% of the duty cycle produces a maximum output voltage of 5 kV, the resulting ozone concentration of 67 ppm. The 30% cycle produces a maximum output voltage of 7.7 kV and ozone production with a concentration of 115.2 ppm. The 50% duty cycle produces a maximum output voltage of 10 kV with an ozone concentration of 134.4 ppm. The 60% duty cycle is capable of generating a maximum output voltage of 10.77 kV with an ozone concentration generated from 160.8 ppm. We found that using 60% duty cycle is capable of producing high concentrations and ozone capacity.